Comparison of endoscopic ultrasound-guided fine-needle aspiration by capillary action, suction, and no suction methods: a randomized blinded study - Bansal, Rinkesh K.; Choudhary, Narendra S.; Puri, Rajesh; Patle, Saurabh K.; Bhagat, Suraj; Nasa, Mukesh; Bhasin, Amit; Sarin, Haimanti; Guleria, Mridula; Sud, Randhir (Endoscopy International Open, 2017)
Background and study aim Different types of endoscopic ultrasound (EUS)-guided fine-needle aspiration (FNA) techniques are used in clinical practice; the best method in terms of outcome has not been determined. The aim of the study was to compare the diagnostic adequacy of aspirated material, and the cytopathological and EUS morphological features between capillary action, suction, and no-suction FNA methods. Patients and methods This was a prospective, single-blinded, randomized study conducted at a tertiary care hospital. Patients were randomized to the three groups: capillary action, suction, and no suction. A total of 300 patients were included, with 100 patients in each arm. Results A total of 300 patients (195 males) underwent EUS-FNA of 235 lymph nodes and 65 pancreatic masses (distribution not statistically different between the groups). The mean age was 52 ± 14 years. A 22 gauge needle was used in the majority (93 %) of procedures. There was no statistical difference between the three groups regarding lymph node size at the largest axis and ratio, type of needle, echo features, echogenicity, calcification, necrosis, shape, borders (lymph nodes), number of passes, and cellularity. Diagnostic adequacy of the specimen was 91 %, 91 %, and 94 % in the capillary, suction, and no suction groups, respectively (P = 0.67). Significantly more slides and blood clots were generated by the suction method compared with the other methods. Conclusion The capillary action, suction, and no suction methods of EUS-FNA are similar in terms of diagnostic adequacy of the specimen. The suction method has the disadvantages of causing more bleeding and generating more slides.